Additive-free aerobic oxidation of hydroazobenzenes: Access to azobenzenes and epoxidation of enones. (12th October 2022) - Lin, Yu; Wu, Hao; Liu, Ziang; Li, Jin; Cai, Rui; Hashimoto, Makoto; Wang, Lei
Graphical abstract: Abstract: We reported herein a highly effective approach to prepare azobenzenes from hydroazobenzenes via an additive-free aerobic oxidation strategy. This method smoothly produces azobenzenes and heterocyclic azo derivatives in DMF at 80 °C under oxygen atmosphere. It features excellent yield, functional group tolerance and convenience. The broad application of this method is further proved by gram scale synthesis and the epoxidation of enones.